Experimental validation of fail-safe hybrid mass damper. (October 2018) - Chesné, Simon; Collette, Christophe
A simple control law, dedicated to improving the performance and stability of hybrid mass dampers, is investigated. The resulting hybrid device is based on decentralized velocity feedback techniques. Two poles and two zeros are added to the initial control law, in order to interact with the dynamics of the structure and the actuator. The interest of these interactions is to change the poles of the closed loop system so as to make the controlled system hyperstable . The margins of gain and phase are therefore infinite. Consequently, the proposed hybrid system controller is fail-safe but also unconditionally stable in theory. Experimentation, using a tuned voice coil actuator, illustrates the performance and robustness of this hybrid control device.